Implementasi Presensi Digital Berbasis Scan Barcode di PKBM Barokah LTF2SM Tegal - fuji alfiyah; Ujianti, Mutiara Handayani (E-Jurnal Universitas Samudra, 2025)
PKBM (Pusat Kegiatan Belajar Masyarakat) is a non-formal education institution focused on developing the skills of learners. PKBM Barokah LTF2SM Talang Tegal, located in Kaladawa Village, Tegal Regency, faces the need for an efficient and accurate attendance system to address challenges in manual methods, such as data loss and recording errors. This study aims to examine the implementation of a digital attendance system based on barcode scanning using Google Forms and Google Spreadsheet to streamline and simplify the attendance process.This qualitative research collected data through observation, interviews, and literature review. The system includes barcode creation, data collection via Google Forms, and automated data processing in Google Spreadsheet. The system offers advantages such as ease of access, reduced human errors, and automatic data storage. However, challenges include dependence on internet connectivity and the need for user training.The study recommends regular training to enhance user skills and periodic evaluations to ensure the system remains relevant. With these steps, the digital attendance system is expected to improve efficiency and support the quality of non-formal education services in the digital era